Dimensioning of painful procedures and interventions for acute pain relief in premature infants - Deise Petean Bonutti; Mariana Firmino Daré; Thaíla Corrêa Castral; Adriana Moraes Leite; Joselaine Aparecida Vici-Maia; Carmen Gracinda Silvan Scochi (Universidade de São Paulo, 2017)
ABSTRACT Objective: to dimension the exposure of premature infants to painful procedures, relating the distribution of the exposure to contextual factors, as well as to describe the pharmacological and non-pharmacological interventions health professionals use during the first two weeks of the infant's hospitalization at two neonatal services. Method: descriptive-exploratory study in which the professionals registered the painful procedures and pain relief interventions on a specific form in the patient file. Results: the daily average of the 89 premature infants was 5.37 painful procedures, corresponding to 6.56 during the first week of hospitalization and 4.18 during the second week (p<0.0001). The most frequent procedures were nasal/oral (35.85%) and tracheal aspirations (17.17%). The children under invasive ventilation were the most exposed to painful procedures (71.2%). Only 44.9% of the painful procedures received some intervention for the purpose of pain relief, the most frequent being sucrose (78.21%) and continuing sedation (19.82%). Conclusion: acute pain was undertreated at these neonatal services, recommending greater sensitization of the team for the effective use of the existing protocol and implementation of other knowledge transfer strategies to improve neonatal pain management.